Pengaruh Senioritas, Prestasi Kerja, dan Motivasi Kerja terhadap Produktivitas Karyawan - Muhammad Syahrul Munir; Hadi Sunaryo; Pardiman Pardiman (UNIVERSITAS ISLAM MALANG, 2020)
Abstract This study aims to describe seniority, work performance, work motivation and productivity of Malang City BPN employees, determine the effect of seniority, achievement, work motivation on employee productivity. This research was conducted in BPN Malang City with a sample of 50 respondents. The data analysis technique uses multiple linear regression analysis. Descriptive analysis results show that Malang City BPN Employees perceive neutrality in all research variabels, namely seniority, work performance, motivation and productivity. Seniority has a significant effect on employee productivity in BPN Malang. Work performance has a significant effect on employee productivity in BPN Malang. Work motivation has a significant effect on employee productivity in BPN Kota Malang. seniority, work performance, and work motivation simultaneously have a significant effect on employee productivity in BPN Malang. Keywords: seniority, work performance, motivation and employee productivity